Coal basically a hazardous Industry and source for numerous occupational diseases for workers - GUPTA, ANUP KRISHNA; DUTTA, AJOY KUMAR; BASU, RITA (IJRDO - Journal of Business Management, 2019)
For the purpose of steady and faster economic growth, plans for development   in all front including industrial units   appear to be  important.Coal plays major rolein the industrial front and building economy .Coal,  the prime  energy   source will    dominate  for  a  few decades to  come  in India  and therefore, attaching importance to existing and  new Coal Projects will gain  priorityCoal mining is a constant struggle with nature.The people  attached  to this industry face challenges in working  against odds  as the industry is known for its highly risky and hazardous working environment. Technological advancement in coal extraction techniques for proliferation of production levels has caused further concern for safety in this industry. A large number of mobile mining equipment such as haul trucks, dumpers, tractors, tankers are used for different operation and such operations contribute significantly in causation of fatal and serious accidents .Fire, flood, collapse, toxic atmospheric contaminant, and dust or gas explosion are the most critical hazardsspecifically linked to underground mining. Besides coal combustion releases mercury, nitrogen oxides, sulfur dioxide and other substances known to be hazardous to human health causing  chronic diseases  and even permanent disablement.